Foreign direct investment in the food industry in Poland - Ambroziak Łukasz (International Journal of Management and Economics)
This article aims to assess the changes in the food industry in Poland (total and including groups and classes of the industry) in 2010–2022 resulting from inflow of foreign direct investment (FDI). The analysis used descriptive statistics methods, total correlation, and partial correlation. The study showed that companies with foreign capital (CFC) are usually larger and have higher productivity than companies with domestic capital (CDC). During the period under study, the difference between CDC and CFC decreased significantly. It may be related to the transfer of technology and knowledge to domestic companies. The study also showed a positive correlation of labor productivity, average salary, and the share of imported supplies in operating costs with the FDI intensity of individual groups and classes of the food industry in Poland. The conducted analysis enriches research on the effects of FDI inflow to the food industry in Poland.